2013
DOI: 10.1136/vr.101658
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing pH of mammary gland secretions is associated with parturition and is correlated with electrolyte concentrations in prefoaling mares

Abstract: The objectives of this study were to determine pH of the mammary gland secretions and the corresponding electrolyte concentrations in prefoaling mares. Pregnant mares (seven primiparous and seven multiparous) were monitored daily from 310-320 days of gestation until parturition. Prefoaling mammary gland secretions were collected, and pH was immediately determined with a pH meter and pH strip test. An aliquot of prefoaling mammary secretions was frozen and stored until further analyses. After parturition, sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 15 publications
4
27
2
2
Order By: Relevance
“…The majority of mares with a pH <7 have been shown to foal within 24 h (Canisso et al . ). Other clinicians have confirmed this; in addition it is possible that the pattern of pH change may reflect fetal maturation (Ellerbrock and Canisso ), which is an exciting prospect for the future.…”
Section: Monitoringmentioning
confidence: 97%
“…The majority of mares with a pH <7 have been shown to foal within 24 h (Canisso et al . ). Other clinicians have confirmed this; in addition it is possible that the pattern of pH change may reflect fetal maturation (Ellerbrock and Canisso ), which is an exciting prospect for the future.…”
Section: Monitoringmentioning
confidence: 97%
“…1984) and pH mammary gland secretions (Canisso et al . 2013) are more precise. The most precise test allows one to estimate approaching labour with accuracy of up to 12 h. Major changes were also documented for sodium concentration, which starts decreasing a few days before parturition, while potassium increases slightly.…”
Section: Routine Management Of the Pregnant Mare In The Stablementioning
confidence: 99%
“…The only method to predict the day of foaling is to identify the increase of calcium concentration in mammary secretions, which occurs 24-12 hours before foaling [4][5][6][7]. More recently, some studies showed a decline of pH in mammary secretion of normal pregnant mares [8][9][10].…”
Section: Introductionmentioning
confidence: 99%